Le jardin Mallarmé : « les fleurs d’abord » - Virginie Pouzet-Duzer (Projets de Paysage)
This article analyses the presence of gardens in Stéphane Mallarmé’s letters, texts and poems. It shows that one of the evocative aspects of Mallarmé’s poetry has to do with the disappearance of these gardens, while flowers and bunches of flowers flourish.